Ice core processing at Dome F, Antarctica - Shoji, Hitoshi; Narita, Hideki; Fujii, Yoshiyuki; Kamiyama, Kokichi; Azuma, Nobuhiko (1994)
P(論文) The Dome F Project is an integrated field and laboratory research effort on deep core drilling and analysis at Dome F, Antarctica. Ice core processing starts immediately after core recovery in the field to combine core drilling activities with core analysis procedures. Key factors in processing procedures include core logging, brittle zone handling, field measurements, sample preparation and core packing for transportation. Designing of a core processing line is quite important to maximize the benefit of the field activity and guide the following laboratory analysis. Functions and tasks of core processing are discussed and a core processing line for Dome F is proposed by taking various requirements and circumstances into consideration. departmental bulletin paper